2011
DOI: 10.1002/ajh.22176
|View full text |Cite
|
Sign up to set email alerts
|

Opioid patient controlled analgesia use during the initial experience with the IMPROVE PCA trial: A phase III analgesic trial for hospitalized sickle cell patients with painful episodes

Abstract: Opioid analgesics administered by patient-controlled analgesia (PCA) are frequently used for pain relief in children and adults with sickle cell disease (SCD) hospitalized for persistent vaso-occlusive pain, but optimum opioid dosing is not known. To better define PCA dosing recommendations, a multi-center phase III clinical trial was conducted comparing two alternative opioid PCA dosing strategies (HDLI-higher demand dose with low constant infusion or LDHI- lower demand dose and higher constant infusion) in 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…The magnitude of patient reported opioid-related withdrawal symptoms was assessed by scripted telephone interview at 3 and 14 days post hospital discharge based on a validated questionnaire. These results have been published elsewhere [30]. …”
Section: Methodsmentioning
confidence: 77%
See 1 more Smart Citation
“…The magnitude of patient reported opioid-related withdrawal symptoms was assessed by scripted telephone interview at 3 and 14 days post hospital discharge based on a validated questionnaire. These results have been published elsewhere [30]. …”
Section: Methodsmentioning
confidence: 77%
“…Opioid usage in the 22 adult participants confirmed the feasibility of the two PCA dosing strategies, while the demand component of the PCA was not used optimally by the 12 pediatric participants [30]. In adults, the 25 mm drop in VAS scores occurred within a median of 2 days for both the HDLI and LDHI treatment groups, with 100% of adults achieving that threshold during the study (Table 2).…”
Section: Methodsmentioning
confidence: 91%
“…It should also be considered that the possibility of interference with late myelination extends beyond opioid abuse and opioid detoxification treatments and could be particularly important in the case of patients within this age bracket subjected to frequent opioid treatments for pain relief. Such is the case of severe pain management in sickle cell disease in which patients are commonly prescribed opioid medications including morphine, methadone, and oxycodone [85]. …”
Section: Discussionmentioning
confidence: 99%
“…Several studies in the surgical literature (14,15) have demonstrated the potential for "fast-tracking" postoperative patients with some success. Additionally, in patients with sickle-cell disease, a lot of research in emergency rooms and outpatient and inpatient settings has been focused on developing the best collaborative approach to minimize resource utilization and improve pain control (16)(17)(18). Another significant issue in IBD patients is nutrition.…”
Section: Discussionmentioning
confidence: 99%